2017
DOI: 10.1021/acs.est.6b05341
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Temporal Trends of Polychlorinated Biphenyls and Their Controlling Sources in China

Abstract: Polychlorinated biphenyls (PCBs) are industrial organic contaminants identified as persistent, bioaccumulative, toxic (PBT), and subject to long-range transport (LRT) with global scale significance. This study focuses on a reconstruction and prediction for China of long-term emission trends of intentionally and unintentionally produced (UP) ∑PCBs (UP-PCBs, from the manufacture of steel, cement and sinter iron) and their re-emissions from secondary sources (e.g., soils and vegetation) using a dynamic fate model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
(143 reference statements)
2
33
0
Order By: Relevance
“…7,8 Much of this attention has arisen because of the presence of PCBs in imported e-wastes. 9,10 Indeed, it was reported that airborne PCBs in China increased from 2004 to 2008 11 at a time when the trend in other parts of the world was the opposite. [12][13][14] PCBs emitted into the atmosphere can originate from both intentionally produced (IP-PCBs) and unintentionally-produced (UP-PCBs) sources.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Much of this attention has arisen because of the presence of PCBs in imported e-wastes. 9,10 Indeed, it was reported that airborne PCBs in China increased from 2004 to 2008 11 at a time when the trend in other parts of the world was the opposite. [12][13][14] PCBs emitted into the atmosphere can originate from both intentionally produced (IP-PCBs) and unintentionally-produced (UP-PCBs) sources.…”
Section: Introductionmentioning
confidence: 99%
“…Because PCBs were intentionally produced chemicals, reliable data on trends in their production are readily available (Table 1). Globally, the production of PCBs worldwide has been estimated at approximately 1.3 million tons (Zhao et al, 2017) and peaked in the 1960s–1970s.…”
Section: Historical Production and Use Of Pcbs Worldwidementioning
confidence: 99%
“…Examples of PCB concentrations in environmental archives from polluted sites are shown in Table 3. Contamination from PCBs within heavily industrialized regions has been mostly caused by leakage from systems containing these compounds (Zhao et al, 2017). Extreme pollution of soils and fluvial sediments close to the condenser plant in the city of Serpukhov (Russia) resulted in Σ 7 PCB concentrations up to 1169 mg/kg in soil and 119 mg/kg in sediment (Malina and Mazlova, (2017).…”
Section: Trends In Pcbs Pollution Recorded In Environmental Archivesmentioning
confidence: 99%
“…This is due to the low environmental concentrations both in China and the rest of the world after production bans were introduced. Unintentionally-produced PCBs have gradually taken a more important role in China, 23 thus human body burdens would be slightly higher for people eating locally sourced food up to 2030. But the unintentional emission of PCBs was only calculated domestically, which may cause potential underestimation for people eating imported food.…”
Section: Impact Of Food Originmentioning
confidence: 99%